La linea dell’orizzonte dell’ethnographic novel tra scrittura autobiografica e Bildungsroman (ACME, 2023)
The contribution aims to investigate the heuristic probing of an increasingly popular expressive medium, the graphic novel. In view of this, analysing the hybridisation between word and image on the one hand in relation to the immediacy of the drawing, and on the other in relation to the degree of psychological depth of the characters, sheds light on the possibility of considering the comic novel as a literary genre in dialogue with the more classical narrative form. Thus, favouring a methodological-theoretical work can lay the appropriate premises for a subsequent focus on a case study. In particular, «La linea dell’orizzonte». Un ethnographic novel sulla migrazione tra Bangladesh, Italia e Londra dialogues not only with the novel form in general, but also with narrative reportage, autobiography and the Bildungsroman, or coming-of-age novel. It is evident that this close dialogue with literary criticism cannot but take into consideration not only a study of the literary genres most in dialogue with The Horizon Line, but also an analysis of the stylistic and thematic peculiarities present in the ethnographic novel with particular attention to the theme of migration.